Emotion recognition, self-knowledge, and perceptions of leisure time activities in emerging adolescents: A longitudinal study. Issue 5 (3rd September 2022) - Bosacki, Sandra; Sitnik, Valentina; Pissoto Moreira, Flavia; Talwar, Victoria
ABSTRACT: This 2-year short-term longitudinal study explored Canadian emerging adolescents' ability to recognize emotions in others, their spontaneous descriptions of themselves and self-understandings, and their narrative and pictorial accounts of themselves engaged in leisure time activities. As part of a larger 5-year longitudinal study, this study describes results from Time 1 (2015–16), 146 Grade 8 students, 97 female, M age = 12.5 y, and Time 2 (2016–17) data from 46 Grade 9 students (33 females; M age = 13.5 y) from eight schools . Participants completed the Reading the Mind in the Eyes Test, self-descriptions, drew and/or wrote a story to describe an enjoyable leisure time activity, and a self-understanding interview (SU). Self-descriptions and stories were also coded for the frequency of mental state language (MSL). Results showed positive correlations between T1 Emotion Recognition (ER) and T1 MSL in drawings of leisure time and between T2 ER and T2 SU. Higher levels of ER in younger adolescents predicted higher levels of SU 1 year later, and T1 SU predicted T2 ER. Across 2 years, ER remained stable, older adolescents scored higher than younger on SU, and girls scored higher than boys on ER. Implications for theory and educational applications are discussed.